Analisis faktor -faktor yang mempengaruhi simpanan mudharabah pada Bank Mandiri Syariah cabang kota Pekanbaru - Devi Yulianti; Anthony Mayes; Syafril Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted in Pekanbaru City in August 2013 to December 2013, with the target customers of Bank Syariah Mandiri branch in Pekanbaru which is located at Jalan Sudirman 450 and some other Branch spread in the city of Pekanbaru. This study aims to determine the factors that influence the Mudaraba Savings Bank Syariah Mandiri branchPekanbaru. This study was performed by using direct interviews to clients through a questionnaire. The samples were extracted using Slovin formulation with an error rate of 10%. The samples in this study were 97 samples of the customer savings and 96 samples of client deposits. Furthermore, the previous studies that underlie the Aulia Mustikasari 2007, concluded that only profit sharing have a positive and significant effect on mudaraba deposits, while income has no effect on Mudaraba Deposits. The results showed that the level of profit-sharing and avoid usury very influential on Mudaraba Deposits in Bank Syariah Mandiri branch Pekanbaru.Keywords: Mudaraba Savings, Profit Sharing Level, Riba